Nahdlatul Ulama and Environmental Engagement in Coastal Bengkalis amid Ecological Crisis - Firdaus, Reno; Siregar, Asfar Hamidi (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
This article explores how Nahdlatul Ulama (NU), through its local branch in Bengkalis (PCNU), responds to the worsening ecological crisis in one of Indonesia’s most vulnerable coastal regions. Using a qualitative case study approach that combines field interviews, participant observation, and document analysis, this study investigates how Islamic environmental ethics—particularly fiqh al-bi’ah and maqāṣid al-sharī‘ah—are translated into collective practices through grassroots religious initiatives. Two key programs are highlighted: Green Pesantren, which integrates ecological education, reforestation, and sustainable practices into Islamic boarding schools; and Mimbar Dakwah, which encourages preachers to include environmental themes in sermons as a form of moral advocacy. These initiatives show how religious discourse can shape environmental behavior and public consciousness at the community level. However, the study also identifies major obstacles, including economic hardship, weak policy enforcement, limited institutional support, and escalating climate impacts. Despite these barriers, PCNU plays a critical role in mobilizing religious networks, shaping local ecological narratives, and promoting community resilience. The findings contribute to the sociology of religion and environmental studies by demonstrating how faith-based organizations can serve as agents of social action and environmental engagement, especially in regions where state capacity is limited.